POTENCY FOR THE UTILIZATION OF RUBBER (Hevea Brasiliensis Muell.Arg) SEED AS AN ALTERNATIVE ENERGY SOURCE OF BIOKEROSENE - Sarma Siahaan Dwi Setyaningsih Hariyadi (Jurnal Teknologi Industri Pertanian, 2009)
Pure plant oil could be obtained from various seeds, such as rubber seed. Rubber seed oil could be converted into biokerosene. The objective of this research was to explore the potency of biokerosene from rubber plantation both smallholder and goverment owned estate (PT. Perkebunan Nusantara). In addition, the ability of rubber seed biokerosene to ignite kerosene stove at households was also evaluated. The experimental design was Block Randomized Factorial in order to evaluate the yield from rubber seed extraction. We also set a Completely Randomized Factorial experiment to learn the influence of peeling and sun drying to the density, viscosity, and FFA (Free Fatty Acid), of extracted oil. Paired-t test was used for analyzing whether the characteristics of crude oil differed from those of biokerosene. The results showed that the oil yield was affected by peeling factor and not by sun-drying. The result showed that peeled rubber seeds yield was higher than that of intact seeds. Yield of crude oil and biokerosene from state owned as well as one from maintained plantation was higher yield than that from smallholder or un-maintained plantation. Factors of peeling and sun-drying did not affect the values of FFA, density and viscosity. Biokerosene added to kerosene could extend the duration of flame. The best mix proportion was 20% biokerosene and 80% kerosene which was further tested with the community on kerosene stoves. Keywords: biokerosene, kerosene stove, oil extraction, rubber seed.